Soil Quality Dynamic and Rice Production of Three Different Rice Farming Systems in Sragen District, Central Java Province - Sukristiyonubowo, Sukristiyonubowo; Widodo, Sugeng; Anshori, Arif; Riyanto, Damasus (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2020)
Abstract. The farmers realize that green revolution technology with high inputs is no longer sustainable, expensive and the yield decrease. Some farmers move to organic rice farming, semi organic, and the rest remain doing conventional rice farming. The research aim was to monitor soil quality dynamic and rice productions under three rice farming systems. This study was conducted in Vertisols at Sambung Macan Sub District, Sragen Regency. The treatments were arranged in randomized complete block design with three replications. The treatments was organic, semi organic and conventional rice farming systems. The results indicated that in organic field, the soil quality in 2019 was more superior than in semi organic and conventional in 2018 and 2017 and soil qualities of semi organic system was better than conventional in terms of soil chemical, physical and biological including soil pH, organic C and total N, P and K total, soil bulk density, particle density, soil porosity and permeability. Similar finding was observed for rice biomass productions in 2019. In 2019 the rice grains yields were 12.68, 7.43 and 7.0, rice straw were 7.25, 6.55 and 6.25 and forrice residues were 4.15, 3.20 and 3.15 tons ha-1 season-1 in organic, semi organic and conventional systems, respectively. Compared to the conventional system, the organic increased about 81%, 16% and 32% for rice grains, rice straw and rice residues, respectively. Compared to conventional, semi organic improved about 6%, 5% and 2% for rice grains, rice straw and rice residues, respectively.Abstrak. Petani menyadari bahwa green revolution technology tidak lumintu, biaya produksi mahal dan hasil panen menurun. Sebagian petani beralih ke budidaya padi organik, semi organik dan sebagian bertahan pada sistem konvensional dengan perbaikan. Penelitian bertujuan untuk mengetahui perkembangan kualitas tanah dan hasil brangkasan padi pada sistem padi organik, semi organik dan konvensional. Penelitian dilaksanakan pada tahun 2017, 2018 dan 2019 pada tiga sistem budidaya padi di Kecamatan Sambung Macan, Sragen. Penelitian menggunakan rancangan acak kelompok, dengan tiga ulangan dan sebagai perlakuan tiga budidaya padi. Hasil penelitian menunjukkan bahwa kualitas tanah pada budidaya organik pada tahun 2019 lebih unggul dibandingkan semi organik dan konvensional pada tahun 2018 dan 2017. Begitu juga kualitas tanah pada semi organik pada 2019 lebih baik dibandingkan budidaya konvensional. Hasil brangkasan padi pada budidaya organik tahun 2019 lebih tinggi dibandingkan dengan tahun 2018 dan 2017 baik pada budidaya padi semi organik maupun konvensional. Hasil gabah, jerami dan sisa panen dari ketiga sistem budidaya padi pada tahun 2019 masing masing sebesar 12,68; 7,43 dan 7,0; jerami 7,25; 6,55 dan 6,25 dan sisa panen 4,15; 3,20 dan 3,15 ton ha-1 musim-1 untuk budidaya padi organik, semi organik dan konvensional. Dibandingkan dengan konvensional sistem, budidaya organik meningkat sekitar 81%, 16% and 32% untuk gabah, jerami dan sisa panen. Dibandingkan dengan konvensional, budidaya semi organik meningkat 6%, 5% and 2% untuk gabah, jerami dan sisa panen.